2021
DOI: 10.1177/17411432211022770
|View full text |Cite
|
Sign up to set email alerts
|

Race and educational leadership: The influence of research methods and critical theorising in understanding representation, roles and ethnic disparities

Abstract: The special issue offers new knowledge about racialised educational experiences by shedding light on racialised leadership in school and higher education in diverse geographical and educational contexts in England, Canada, America and South Africa through a mix of research methods (phenomenological, longitudinal, documentary, semi-structured interviews), analytical (content and textual analysis) and theoretical approaches (critical race theory [CRT], critical ecological). This special issue prioritises the cen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 33 publications
1
5
0
Order By: Relevance
“…They report that, regardless of their gender, the department chairs with more administrative power are more likely to commit to gender diversity in STEM. These findings about increasing the representation of women faculty in STEM confirm other research findings (Howard & Gagliardi, 2018;Maylor et al, 2021) about the power middle management plays in producing these outcomes.…”
Section: Challenges Faced By Black Administrators In Higher Educationsupporting
confidence: 87%
“…They report that, regardless of their gender, the department chairs with more administrative power are more likely to commit to gender diversity in STEM. These findings about increasing the representation of women faculty in STEM confirm other research findings (Howard & Gagliardi, 2018;Maylor et al, 2021) about the power middle management plays in producing these outcomes.…”
Section: Challenges Faced By Black Administrators In Higher Educationsupporting
confidence: 87%
“…This feeling of racial divide can contribute to and exacerbate a sense of exclusion of non-White students/practitioners from social work teams, organisations, networks and, for some, the profession as a whole. The lack of non-White social workers in leadership roles in the UK highlights the impact of the wider systemic oppression that is reflected in the social work profession (Maylor et al, 2021;Ishaq and Hussain, 2022). It moves away from just individuals or the institutional examples of oppression that were previously highlighted, and presents the issue on more of a macro-level.…”
Section: Discussionmentioning
confidence: 99%
“…It moves away from just individuals or the institutional examples of oppression that were previously highlighted, and presents the issue on more of a macro-level. Previous studies aiming to try and understand why non-White professionals do not advance in their social work careers showed that discriminatory practice, lack of role models and 'organisational' barriers were some of the causes (Brockmann et al, 2001;Maylor et al, 2021). However, despite this being highlighted in social work research, little has been done in terms of strategy and initiatives to overcome this.…”
Section: Discussionmentioning
confidence: 99%
“…The narrative methodology often involves social constructivism, where the researcher and participant make meaning as co-constructors about the participant's experiences (Hickson, 2016). Within narrative research and storytelling is also the counter-story, which allows stories from marginalized groups to be shared, offering a differing perspective (Maylor et al, 2021).…”
Section: Narrative Researchmentioning
confidence: 99%